EFFECT OF SIX HATS IN THE DEVELOPMENT OF LANGUAGE SKILLS OF KINDERGARTEN CHILDREN (Journal of the College of Education for Women, 2019)
Increasing need for day after day to find ways and innovative means ofhelping to educate and give children the skills of different kind, has found aresearcher on the subject of hats, six room to give children language skillsthrough the experience of field reconnaissance conducted on the threechildren found that language skills improved, he decided to make these study.Objectives of the study:Understand the differences between the experimental group first (the way thedebate) and second (six caps) depending on the test post administration.to identify the language skills of the second group according to the pre andpost testDifferences between males and females in the second group (Six Hats)Search Tools: A measure of language skills Setup (al-Baghdadi, 2005) as wellas the positions of video when you use the hats that he created (Bono.)Search Results:1 - The effect of the six caps in the growth of language skills more than thedebate2 - there is no difference between males and females in the growth of socialskills2- Recommendations:- Using the Six Hats in the education of children.- Teacher training courses on dealing with students are encouraged to think ofscientific reasoning.- Proposals:- A study for the detection of speech defects in children using the six hatsRiyadh.- A study on the feasibility of the six hats according to the variables of timeand effort.